2018
DOI: 10.1523/eneuro.0402-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Primary Afferent-Derived BDNF Contributes Minimally to the Processing of Pain and Itch

Abstract: BDNF is a critical contributor to neuronal growth, development, learning, and memory. Although extensively studied in the brain, BDNF is also expressed by primary afferent sensory neurons in the peripheral nervous system. Unfortunately, anatomical and functional studies of primary afferent-derived BDNF have been limited by the availability of appropriate molecular tools. Here, we used targeted, inducible molecular approaches to characterize the expression pattern of primary afferent BDNF and the extent to whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 50 publications
(93 reference statements)
6
26
0
1
Order By: Relevance
“…Specifically, depletion of DRG macrophages prevented the upregulation of Bdnf in the DRG that occurred within 24 h of SNI. Importantly, despite reports of BDNF synthesis by microglia 45 and presumably macrophages, consistent with other findings 36,46 , our ISH analysis only detected Bdnf mRNA in sensory neurons. On the other hand, as conditional deletion of BDNF from sensory neurons has minimal to no effect on the mechanical allodynia induced by nerve injury 34,36 , to what extent the macrophage contribution to Bdnf upregulation in sensory neurons influences nociceptive processing is not clear.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Specifically, depletion of DRG macrophages prevented the upregulation of Bdnf in the DRG that occurred within 24 h of SNI. Importantly, despite reports of BDNF synthesis by microglia 45 and presumably macrophages, consistent with other findings 36,46 , our ISH analysis only detected Bdnf mRNA in sensory neurons. On the other hand, as conditional deletion of BDNF from sensory neurons has minimal to no effect on the mechanical allodynia induced by nerve injury 34,36 , to what extent the macrophage contribution to Bdnf upregulation in sensory neurons influences nociceptive processing is not clear.…”
Section: Discussionsupporting
confidence: 88%
“…As qPCR could not determine whether the increased Bdnf derived only from sensory neurons or also from surrounding non-neuronal cells, we used in situ hybridization (ISH) to examine the DRG. Figure 5d, e shows that upregulation of Bdnf mRNA is readily detected in sensory neurons one day after nerve injury (POD1), but we found no expression in surrounding nonneuronal cells, in line with our previous report 36 . Consistent with the qPCR analysis, quantification of ISH intensity in VEH-treated mice demonstrated a threefold induction of Bdnf in the ipsilateral compared with the contralateral DRG (Fig.…”
Section: Ap Treatment Does Not Alter Spinal Cord Microglia Numbersupporting
confidence: 92%
“…Although a majority of studies have indicated that increased expression of BDNF in the spinal cord induces pain hypersensitivity, [31][32][33] some studies also reported that BDNF exerted limited pronociceptive effect and even antinociceptive effect on the pain. [34][35][36] Previous studies indicated that Shh signaling activation in the cavernous and sciatic nerves up-regulated BDNF expression. 10 Liu et al found that Shh signaling activation significantly elevated BDNF expression in the spinal cord of morphine-induced hyperalgesia rats, and administration of K252, an antagonist of BDNF, attenuated the thermal allodynia induced by SAG.…”
Section: Discussionmentioning
confidence: 99%
“…The microglia source of BDNF has good genetic (Sorge et al, 2015), pharmacological and immunolabeling support (Ramer et al, 2007) however it remains controversial. Embryonic fate mapping experiments and in situ hybridization have suggested that BDNF is not expressed in naïve spinal microglia (Dembo et al, 2018) and sequencing evidence suggests an absence of Bdnf transcripts in spinal microglia after partial nerve injury (Denk et al, 2016), so repeating the lineage tracing experiments in the context of nerve injury will be essential for resolution. Together, microglia play an important role in increasing nociceptive sensitivity by providing pro-inflammatory factors, functioning similarly to peripheral immune cells, although their exact roles remain unclear and the pathways are not convincingly established.…”
Section: Microglial Activationmentioning
confidence: 99%